2009
DOI: 10.1136/oem.2008.041277
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on occupational risk factors for sino-nasal cancer

Abstract: Objectives: Sino-nasal cancer has been consistently associated with exposure to wood dust, leather dust, nickel and chromium compounds; for other occupational hazards, the findings are somewhat mixed. The aim of this study was to investigate the risk of sino-nasal epithelial cancer (SNEC) by histological type with prior exposure to suspected occupational risk factors and, in particular, those in metalworking. Methods: Between 1996 and 2000, incident cases were collected on a monthly basis from hospitals throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
1
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 36 publications
4
69
1
17
Order By: Relevance
“…Intestinal type adenocarcinoma (28% -41.8%) was the second most frequent histopathology after adenocarninoma with no other specification. Twentythree patients (34.3%) had tumor extension to orbit (9), skull base (2), orbit and skull base (8) and others places like pterigopalatine fossa and cheek (5). According to T stages, 1 (1.5%) patient was T1, 19 (28.4%) T2, 21 (31.3%) T3, 21 (31.3%) T4a and 5 (7.5%) T4b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal type adenocarcinoma (28% -41.8%) was the second most frequent histopathology after adenocarninoma with no other specification. Twentythree patients (34.3%) had tumor extension to orbit (9), skull base (2), orbit and skull base (8) and others places like pterigopalatine fossa and cheek (5). According to T stages, 1 (1.5%) patient was T1, 19 (28.4%) T2, 21 (31.3%) T3, 21 (31.3%) T4a and 5 (7.5%) T4b.…”
Section: Resultsmentioning
confidence: 99%
“…The average age for presentation is 50 -60 years, with male predominance (2 -4:1) [4,7]. Epidemiologically, adenocarcinoma has been associated with workers exposed to hardwood dust since this relation was first reported in 1965 by MacBeth [1,8]. These are mostly intestinal-type sinonasal adenocarcinomas and show a strong preference for the ethmoid sinus [4].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial tumours represent over two/third of the SNC and, among them, the most common histotypes are adenocarcinoma and squamous cell carcinoma (SCC) (2) with European studies showing a frequency of adenocarcinoma (3)(4)(5) higher than that reported in the corresponding Northern American studies (6,7) . Other less common sinonasal epithelial histologies are adenoid cystic cancer (ACC) and undifferentiated carcinoma (SNUC).…”
Section: Introductionmentioning
confidence: 97%
“…Occupational risk factors that have been related with a higher incidence of SNC include wood dust (13) , leather dust (14) , nickel compounds and hexavalent chromium (15) , formaldehyde and other solvents (2,16) and polycyclic aromatic hydrocarbons (PAHs) (17) .…”
Section: Introductionmentioning
confidence: 99%
“…While occupational exposures to some chemical and physical agents are known to be risk factors for several cancer types [7][8][9][10][11], little is known regarding the role of occupational factors in the development of meningioma [3]. Some studies have shown associations between specific works (e.g.…”
Section: Introductionmentioning
confidence: 99%